Overview of abortion cases with severe maternal outcomes in the WHO Multicountry Survey on Maternal and Newborn Health: a descriptive analysis. (March 2014) - Dragoman, M; Sheldon, WR; Qureshi, Z; Blum, J; Winikoff, B; Ganatra, B; ,
Abstract : Objective: To summarise individual and institutional characteristics of abortion‐related severe maternal outcomes reported at health facilities. Design: Secondary analysis of data from the WHO Multicountry Survey on Maternal and Newborn Health. Setting: 85 health facilities in 23 countries. Sample: 322 women with abortion‐related severe maternal outcomes. Methods: Frequency distributions and comparisons of differences in characteristics between cases of maternal near miss and death using Fisher's exact tests of association. Main outcome measures: Individual and institutional characteristics and frequencies of potentially life‐threatening conditions, and interventions provided to women with severe maternal outcomes, maternal near miss, and maternal death. Results: Most women with abortion‐related severe maternal outcomes (SMOs) were 20–34 years old (65.2%), married or cohabitating (92.3%), parous (84.2%), and presented with abortions resulting from pregnancies at less than 14 weeks of gestation (67.1%). The women who died were younger, more frequently without a partner, and had abortions at ≥14 weeks of gestation, compared with women with maternal near miss (MNM). Curettage was the most common mode of uterine evacuation. The provision of blood products and therapeutic antibiotics were the most common other interventions recorded for all women with abortion‐related SMOs; those who died more frequently had antibiotics, laparotomy, and hysterectomy, compared with women with MNM. Although haemorrhage was the most common cause of abortion‐related SMO, infection (alone and in combination with haemorrhage) was the most common cause of death. Conclusion: This analysis affirms a number of previously observed characteristics of women with abortion‐related severe morbidity and mortality, despite the fact that facility‐based data on abortion‐related SMO suffers a number of limitations.